2021
DOI: 10.1177/17479541211002977
|View full text |Cite
|
Sign up to set email alerts
|

Strength training for throwing velocity enhancement in overhead throw: A systematic review and meta-analysis

Abstract: The overhead throw is a fundamental technical-tactical ability for overhead sports. The purposes of this review are to assess the effect of resistance training (RT) in enhancing throwing velocity in athletes and to investigate the relationships between age or gender in this effect. Control group trials were identified through looking up electronic databases with a search span of 10th December 2020. Only studies which have control groups within research design, subjects randomly assigned to groups, healthy athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Currently, there is evidence of the use of constant resistance as a methodology to generate PAPE [58,59]. These studies have shown that significant throwing speed increases by using constant resistance as neuromuscular activation [60][61][62].…”
Section: Variable Resistance and Throwing Speedmentioning
confidence: 99%
“…Currently, there is evidence of the use of constant resistance as a methodology to generate PAPE [58,59]. These studies have shown that significant throwing speed increases by using constant resistance as neuromuscular activation [60][61][62].…”
Section: Variable Resistance and Throwing Speedmentioning
confidence: 99%
“…Athletes need to pay attention to the training of children' s flexibility, physical coordination, flexibility, and other comprehensive abilities. 8 With the continuous improvement of children's various functions and ages, the training of special abilities should also be improved accordingly. Increase the intensity and intensity of training according to the child's specific situation.…”
Section: Pay Attention To Children's Comprehensive Physical Developmentmentioning
confidence: 99%
“…Two independent data extractors (F.J.B.-D. and D.M.-G.) followed a previously established protocol to extract the data (52). If differences or inconsistencies were found, a third reviewer (D.J.-M.) discussed the study data until an agreement was reached about the data validity.…”
Section: Data Extractionmentioning
confidence: 99%